Pengembangan Gerabah Sebagai Ekonomi Kreatif Berbasis Budaya Masyarakat Compang Desa Golo Kempo - Dewi Putri Jehana, Klaudia; ., Aliffiat; Suarsana, I Nyoman (Sunari Penjor : Journal of Anthropology, 2021)
The village Golo Kempo has two village children namely Compang village and Rambang village. Compang village is known as the only village pottery maker. The ancestors of the Compang community also made pottery made by the ancestors to make ends meet. In 2017 a group of 10 people was formed and worked on product development. The result of multiple performance groups and so on in peripherals, are not just the third type local made by ancestors.  The study centers on learning the factors that led to the development of Compang societies as a culturally based creative economy and to learn the implications of its development for the people of the study using qualitative research methods that ethnographic research models by observation techniques, interviews and literature studies supporting the study are the interviews, recording tools, camera and writing tools.